Percutaneous extraction of big kidney stone without fragmentation: The novel technique in percutaneous nephrolithotomy (EN BLOC PCNL) - Karami, Hormoz (Urol Case Rep, 2021)
PCNL is gold standard treatment of pelvis stone more than 2 cm. Since 1970 that PCNL was introduced, multiple methods including mini PCNL, Lap assisted PCNL etc. were used to increase the efficacy and decrease the complications of PCNL in different patients. We describe a new method of PCNL for the first time for extracting 7 cm renal stone without fragmentation, and we called it EN BLOC PCNL. Our technique had no complication and caused lower operative time.